Left sided Scimitar syndrome - Sabyasachi Pandey; Adaligere Paraswanath Bharath; Aditya P Mohata; Ashita Barthur; Anand P Subramanian; Mahimarangaiah Jayranganath (Wolters Kluwer Medknow Publications, 2023)
The images depict a rare case of Scimitar syndrome involving the left lower pulmonary vein.